Evidence, Theory and Context: Using intervention mapping to develop a worksite physical activity intervention - McEachan, Rosemary RC (BioMed Central, 2008)
BACKGROUND: The workplace is an ideal setting for health promotion. Helping employees to be more physically active can not only improve their physical and mental health, but can also have economic benefits such as reduced sickness absence. The current paper describes the development of a three month theory-based intervention that aims to increase levels of moderate intensity physical activity amongst employees in sedentary occupations. METHODS: The intervention was developed using an intervention mapping protocol. The intervention was also informed by previous literature, qualitative focus groups, an expert steering group, and feedback from key contacts within a range of organisations. RESULTS: The intervention was designed to target awareness (e.g. provision of information), motivation (e.g. goal setting, social support) and environment (e.g. management support) and to address behavioural (e.g. increasing moderate physical activity in work) and interpersonal outcomes (e.g. encourage colleagues to be more physically active). The intervention can be implemented by local facilitators without the requirement for a large investment of resources. A facilitator manual was developed which listed step by step instructions on how to implement each component along with a suggested timetable. CONCLUSION: Although time consuming, intervention mapping was found to be a useful tool for developing a theory based intervention. The length of this process has implications for the way in which funding bodies allow for the development of interventions as part of their funding policy. The intervention will be evaluated in a cluster randomised trial involving 1350 employees from 5 different organisations, results available September 2009.